2022
DOI: 10.1002/inf2.12358
|View full text |Cite
|
Sign up to set email alerts
|

A shape memory scaffold for body temperature self‐repairing wearable perovskite solar cells with efficiency exceeding 21%

Abstract: Grain boundary cracks in flexible perovskite films can be repaired by filling with self-repairing polymers during the preparation and wearable operation.However, the self-repairing polymers are commonly active through external heating or humidification treatments, which cannot match with the human body's temperature tolerance of wearable devices. Herein, a body temperatureresponsive shape memory polyurethane (SMPU) is demonstrated to achieve the real-time mechanical self-repairing of grain boundary cracks (~37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…Specifically, R s and R rec are the series resistance and the recombination resistance of the devices, respectively. [ 47 ] It shows that the recombination resistance of the clean‐passivate device increases significantly, indicating a suppression of non‐radiative recombination due to defect passivation. Kelvin probe force microscopy (KPFM) also demonstrates that the surface electrical properties of the perovskite has been changed by clean‐passivation method, with more uniform potential distribution, as shown in Figure S20 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, R s and R rec are the series resistance and the recombination resistance of the devices, respectively. [ 47 ] It shows that the recombination resistance of the clean‐passivate device increases significantly, indicating a suppression of non‐radiative recombination due to defect passivation. Kelvin probe force microscopy (KPFM) also demonstrates that the surface electrical properties of the perovskite has been changed by clean‐passivation method, with more uniform potential distribution, as shown in Figure S20 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Reproduced with permission. [ 126 ] Copyright 2022, Wiley‐VCH. D) Optical microscope images of the self‐healing process: cracks changed process in the crosslinked TA‐NI film at room temperature (about 35 °C) over time.…”
Section: Additive Engineering In Fpscsmentioning
confidence: 99%
“…To make FPSCs more suitable for wearable electronic products, Xue et al reported a temperature‐responsive (37 °C) shape memory polyurethane (SMPU) for real‐time self‐healing of FPSCs grain boundary cracks. [ 126 ] In addition, SMPU is uniformly distributed at the grain boundaries of the perovskite film to form a crosslinked network, which enhances the grain size and passivates the grain boundary defects and greatly releases the mechanical stress (Figure 9C). Therefore, the leaf‐coated FPSCs with SMPU achieved a 21.33% champion PCE.…”
Section: Additive Engineering In Fpscsmentioning
confidence: 99%
“…[5][6][7][8][9] Their superior mechanical, thermal, and conductive performance provides a broad application prospect in energy storage, pollutant adsorption, heat insulation, electromagnetic shielding, flexible sensing, catalysis and other fields. [10][11][12][13][14][15] Graphene aerogel is a kind of macroscopic material assembled from graphene or its derivatives, with an interconnected porous network structure, which is also known as graphene foam or graphene sponge. Although the bulk form of graphene aerogel has shown functional applications in many aspects, its development from a macroscopic scale toward miniaturized patterns is of great importance for the realization of high-performance integrated devices.…”
Section: Introductionmentioning
confidence: 99%